PERAN ORANG TUA DALAM PEMILIHAN PROGRAM TAYANGAN GAWAI PADA ANAK USIA DINI DI TK X JEMBER - Rachman, Angraeny Unedia; Kusumaningtyas, Nuraini; Endang Jatmikowati, Tri (Early Childhood: Jurnal Pendidikan, 2024)
Excessive use of gadgets and internet access at an early age can affect a child's growth and development. The results of the research aim to determine the role of parents in selecting gadget broadcast programs for early childhood. The method used is a descriptive quantitative method. The research results show that 72.34% of parents only occasionally view and control what shows their children access and consume. 8.51% of them actually choose shows that are suitable for their children, do not give children the freedom to choose the shows they want to watch themselves, and 19.14% of parents give their children freedom to use devices and to play with devices, as long as they don't fuss and bother their parents. It was concluded that parents need an active role in assisting the use of devices and internet access to monitor and control the content of shows that can be seen by children. Although each group of parents has its reasons regarding the mentoring role that has been carried out, basically monitoring must be carried out so that parents have sufficient knowledge regarding children's behavior, and establish signs, rules and instructions for their growth and development.